Dietary fiber-based regulation of bile salt hydrolase activity in the gut microbiota and its relevance to human disease. (31st December 2022) - Kastl, Arthur; Zong, Wenjing; Gershuni, Victoria M.; Friedman, Elliot S.; Tanes, Ceylan; Boateng, Adoma; Mitchell, William J.; O'Connor, Kathleen; Bittinger, Kyle; Terry, Natalie A.; Bales, Christina; Albenberg, Lindsey; et al.
ABSTRACT: Complications of short bowel syndrome (SBS) include malabsorption and bacterial overgrowth, requiring prolonged dependence on parenteral nutrition (PN). We hypothesized that the intolerance of whole food in some SBS patients might be due to the effect of dietary fiber on the gut microbiome. Shotgun metagenomic sequencing and targeted metabolomics were performed using biospecimens collected from 55 children with SBS and a murine dietary fiber model. Bioinformatic analyses were performed on these datasets as well as from a healthy human dietary intervention study. Compared to healthy controls, the gut microbiota in SBS had lower diversity and increased Proteobacteria, a pattern most pronounced in children on PN and inversely correlated with whole food consumption. Whole food intake correlated with increased glycoside hydrolases (GH) and bile salt hydrolases (BSH) with reduced fecal conjugated bile acids suggesting that dietary fiber regulates BSH activity via GHs. Mechanistic evidence supporting this notion was generated via fecal and plasma bile acid profiling in a healthy human fiber-free dietary intervention study as well as in a dietary fiber mouse experiment. Gaussian mixture modeling of fecal bile acids was used to identify three clinically relevant SBS phenotypes. Dietary fiber is associated with bile acid deconjugation likely via an interaction between gut microbiota BSHs and GHs in the small intestine, which may lead to whole food intolerance in patients with SBS. This mechanism not only has potential utility in clinical phenotyping and targeted therapeutics in SBS based on bile acid metabolism but may have relevance to other intestinal disease states.